The remarkable UV light invulnerability of thymine GNA dinucleotides. Issue 83 (2nd October 2019) - Coantic-Castex, Stéphanie; Martinez, Agathe; Harakat, Dominique; Guillaume, Dominique; Clivio, Pascale
Abstract : The thymine moieties of GNA dinucleotides exhibit resistance to UV light due to the absence of a stacked conformation suitable for photochemical reaction. Abstract : We herein demonstrate the UV resistance of glycol nucleic acid (GNA) dinucleotides. This resistance sustains the hypothesis of GNA as a nucleic acid prebiotic ancestor on early Earth, a time of intense solar UV light. Such photorobustness, due to the absence of intrastrand base stacking, could offer an opportunity for nanodevice development requiring challenging UV conditions.